Impact of Enforcing Sharia Regional Regulations During the Covid-19 Pandemic - Achir, Nuvazria; I. Rahim, Erman (KnE Social Sciences, 2022)
This study aims to find out field facts related to the effect of implementing regional legal products, namely Regional Regulations (Peraturan Daerah) with a Religious (Shari’ah) nuance, especially during the COVID-19 pandemic which has an impact not only on legal social problems but also on the economy due to restrictions on the movement of community activities (PPKM). Based on this condition, the government is required to be more creative and innovative in overcoming problems in society, including poverty. Local regulations are required to contribute to the community, not only in normal conditions but also during an emergency. This study uses empirical legal research methods with a case approach. The results of the study show that: The implications or impacts of implementing regulations with sharia nuances during the pandemic, especially with regard to the Al-Qur’an Reading and Writing Regional Regulations and the Zakat Regional Regulations can partially facilitate the task of regional heads in handling social affairs, both regarding education, especially in eradicating Al-illiteracy. The Qur’an in which society creates independence through the efforts of each individual to develop themselves, both through formal and non-formal education, including the process of carrying out their obligations as God’s creatures. The existence of the Regional Regulation on Zakat is able to support the development and the community’s economy in the midst of an uncertain situation due to the pandemic, through the distribution of direct assistance, both in the form of business capital money and means of transportation (bentor). Together with the National Amil Zakat Agency (Baznas), the local government also intervenes in low-income communities in each sub-district gradually. As a recommendation, local governments need to maximize the provisions of regional regulations with sharia nuances to support development in the field of formal and non-formal education, by accommodating the regulatory substance of the learning process in the pandemic era. The regional regulations on zakat need to be maintained and improved in order to support the community’s economy by expanding the income pool, increasing programs, and targeting communities as recipients of assistance. Keywords: impact, Sharia regional regulations, Covid 19 pandemic